KAJIAN EKSPERIMEN PENGARUH DIAMETER PLUNGER POMPA INJEKSI BAHAN BAKAR PADA PERFORMA DAN GAS BUANG MESIN DAIHATSU TAFT DIESEL DL62 - Joni Dewanto; Teng Sutrisno; Nicolas G. W. Wardana (Jurusan Teknik Mesin Universitas Negeri Surabaya, 2023)
For classic car lovers, the appearance of the Daihatsu Taft in the nineties was no less interesting than today's SUVs. However, the power is not comparable, because the Daihatsu Taft diesel engine still uses old technology. This research is an attempt to improve the performance of old diesel engines, which do not use common rail systems. Specifically, to determine the effect of modifying the size of the plunger of the fuel injection pump, on engine power and torque, fuel consumption and exhaust gas opacity. The analysis was carried out through a comparative study of the performance of standard machines and machines with modified plunger sizes I and II which were larger than the standard plunger diameter. Testing the performance of the machine using a Dastek Dynamometer 2WD Plate Roller. The results showed that the larger the plunger diameter of the injection pump, the effect of increasing power, torque, fuel consumption rate and exhaust gas opacity as well as the efficiency of the Daihatsu Taft DL62 diesel engine. The increase in exhaust gas opacities of modified engines does not exceed and is still far below the maximum threshold according to the Regulation of the State Ministry of Environment No. 5 of 2006 concerning Thresholds of Exhaust Emissions of Old Motor Vehicles. The emission test method uses ISO 11614